THE DETERMINANTS OF JOB STRESS AND ITS INFLUENCE ON EMPLOYEES’ WELL-BEING - Nurul Athirah Sukor; Norhanisah Mohd Zaide; Nursyazwani Samsul; Nor Syahidah Azman; Kamarul Haizam Samli; Siti Nurul Akma Ahmad (International Journal of Accounting, Finance and Business, 2022)
This article is discussing about job stress and how it has been linked to well-beingamongst people working in different working environments. The previous studies on the factorsof work stress and how it might impact the well-being of employees is reviewed in this researcharticle. The review clarifies the concept of workplace stress, as well as the individual wellbeingand working characteristics of employees. Job stress is indeed a major contributor toorganizational poor performance and lowers job satisfaction. This study aims to investigate thedeterminants factors of job stress and how its influence one's well-being. Based on the reviews,workload, longer working hours, lack the reciprocity of fairness are the most commoncontributing factors for job stress. This review will benefit to the manager and organization toachieve their organizational goals by providing an intervention program of work stress amongemployees.